Upaya Meningkatkan Kemampuan Berpikir Tingkat Tinggi (Hots) Melalui Metode Andragogi MTs Swasta Al-Ikhlas di Pangkalan Susu - Hayatun Sabariah; Diani Syahfitri; Dhea Rizki Insani R; Firza Al Qadri (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2020)
The purpose of this study was to identify how to improve higher order thinking skills (HOTS) in MTs students MTs. Swasta Al-Ikhlas Pangkalan Susu. This study uses a classroom action research method that uses several cycles that aim to improve higher order thinking skills (HOTS). Each cycle carried out 4 stages, planning, action, observation, reflection. In first cycle , the learning outcomes of class VIII MTs Al-Ikhlas Pangkalan Susu are still low, from 26 students, 20 students complete or 76.9%, while 6 students or 23.1% have not achieved complete learning with an average score 73. In the second cycle after making improvements in the first cycle, it can be seen that the learning outcomes of class VIII students at MTs Swasta Al-Ikhlas Pangkalan Susu have reached minimum completeness (KKM 70) with an average value of 76. From the results of research conducted by researchers, using the Andragogy Method in the learning process can improve students' higher order thinking skills (HOTS). This can be seen from the improvement indicators from the results of the research first cycle to second cyclecontinue to increase. There was an increase in student learning outcomes, which was originally the average score in the first cycle test of 73 and the second cycle of 76 increased by a difference of 3. This indicates that student learning outcomes are increasing and are included in the very high category.